Green Digital Leadership and Sustainable Innovation Capability in Vietnamese Manufacturing: The Roles of Green Organizational Culture, Digital Transformation Readiness, and Environmental Turbulence - Nguyen, Thanh Binh (International Journal of Energy Economics and Policy, 2026)
In the context of increasing demands for sustainable development and digital transformation, manufacturing enterprises in Vietnam are facing stronger innovation pressure than ever before. This study aims to assess the impact of Green Digital Leadership (GDL), Green Organizational Culture (GOC), and Digital Transformation Readiness (DTR) on firms’ Sustainable Innovation Capability (SIC). At the same time, the study examines the moderating role of Environmental Turbulence (ET) in the relationship between GDL and SIC. Data were collected from 232 manufacturing enterprises in Vietnam and analyzed using statistical techniques including Cronbach’s Alpha, Pearson correlation, multiple regression, and interaction testing. The results show that GDL, GOC, DTR, and ET all have positive and statistically significant effects on SIC, in which GOC demonstrates the strongest influence. However, ET does not moderate the relationship between GDL and SIC. These findings contribute additional empirical evidence on sustainable innovation in the context of an emerging economy and provide important managerial implications for Vietnamese enterprises in their journey toward green digital transformation.